Biomechanics of the pole vault - Schade, F. (3rd European Pole Vault Conference - Köln 2008, 2008)
Author presents recent findings on the biomechanics of the polevault: I. Energy exchange concept - Pole Vault - F. Schade/A. Arampatzis II.IOC/IAAF project - pole vault - F. Schade/A. Arampatzis/G.-P. Brüggemann/J. Isolehto/P. Komi III.Experimental study - JPC - F. Schade/A. Arampatzis Based on an introduction to energy transformation processes in the pole vault Falk Schade gave a comparison of the findings in biomechanical studies from 1997 to 2005. He showed that there have been no significant developments in the men's pole vault, while the technical development in the women's pole vault shows a significant rise of the interaction between the vaulters and their poles. In the next step he showed that inter-individually as well as intra-individually the increase of runup speed results in a loss of the mechanical quality of the vaulter-pole-interaction during the jump itself. This means that each vaulter has to decide individually where to he or she is aiming with her individual training strategy. In his last part he showed that in an experimental study he found no evidence on the concept of the "free takeoff": The energy balance of the jump-and-plant complex was not influenced by the moment of the pole plant being early or late during the takeoff action.